Managing routines and keeping on track: technology, human cognition and performativity in SMEs. Issue 3 (4th January 2022) - Costa Júnior, Júlio César da; Nascimento, Leandro da Silva; Jerônimo, Taciana de Barros; Granja, Brunna Carvalho Almeida
Abstract : Purpose: Routine dynamics provide a robust theoretical framework to explore a wide range of organizational phenomena. However, the study of routines and the effect of technology on its performativity in small and medium-sized enterprises (SMEs) still lack attention by researchers. This paper aims to analyze how the balance between process technology and human cognition affects routines' performativity in SMEs. Design/methodology/approach: It was conducted a multicase study composed of Brazilian SMEs in the bakery industry. Data collection took place through interviews with managers and employees, observation of operational processes and document analysis. Thematic content analysis was adopted for categorization and data analysis. Findings: The authors' findings allow inferring there is no primacy of a more automated or artisanal production process to achieve competitiveness, which breaks the paradigm of the superior performance of automated production over the artisanal process that haunts SMEs. Though technology increases production efficiency, the artisanal approach can be valuable at promoting a company by commercially using this know-how to explore other business models appreciated by the public. Practical implications: The authors' proposals became relevant in a practical perspective once it works as a parameter for SME managers' decision-making about new investments in production resources and to foster public policies and other actions developed by support services for small businesses. Originality/value: This study expands the frontiers in routines literature on SMEs, which lacks deepening. From this, SME managers can intensify actions to optimize process routines performativity through technologies or human cognition to keep the routines on track.